Vanadium Redox Flow Batteries Using meta-PolybenzimidazoleBased Membranes of Different Thicknesses - Noh, Chanho; Jung, Mina; Henkensmeier, Dirk; Nam, Suk Woo; Kwon, Yongchai (American Chemical Society, 2017)
15, 25, and 35 mu m thick meta-polybenzimidazole (PBI) membranes are doped with H2SO4 and tested in a vanadium redox flow battery (VRFB). Their performances are compared with those of Nafion membranes. Immersed in 2 M H2SO4, PBI absorbs about 2 mol of H2SO4 per mole of repeat unit. This results in low conductivity and low voltage efficiency (VE). In ex-situ tests, meta-PBI shows a negligible crossover of V3+ and V4+ ions, much lower than that of Nafion. This is due to electrostatic repulsive forces between vanadium cations and positively charged protonated PBI backbones, and the molecular sieving effect of PBI's nanosized pores. It turns out that charge efficiency (CE) of VRFBs using meta-PBI-based membranes is unaffected by or slightly increases with decreasing membrane thickness. Thick meta-PBI membranes require about 100 mV larger potentials to achieve the same charging current as thin meta-PBI membranes. This additional potential may increase side reactions or enable more vanadium ions to overcome the electrostatic energy barrier and to enter the membrane. On this basis, H2SO4-doped meta-PBI membranes should be thin to achieve high VE and CE. The energy efficiency of 15 mu m thick PBI reaches 92%, exceeding that of Nafion 212 and 117 (N212 and N117) at 40 mA cm(-2).